A case of ovarian Teratoma with nephroblastoma presenting abdomen metastasis. Issue 5 (29th March 2022) - Wu, Yinan; Chu, Chu; Zhang, Jingyuan; Nitish, Beharee; Ni, Jing; Xu, Xinyu
Abstract: Background: Teratoma with nephroblastoma (TWN) is an extremely rare condition. Since 1984, only 45 reported cases have been identified. To our knowledge, there have been only two cases of TWN of ovarian origin. Case presentation: We described a case of ovarian TWN who presented to us with painless abdominal masses 6 months after undergoing right ovarian cystectomy. The tumor had spread to the abdomen due to spontaneous rupture of the ovarian cyst and failure to undergo chemotherapy. Microscopically, the ovarian mass exhibited the typical components of a mature cystic teratoma. The tumors found in both the ovary and abdomen contained the nephroblastoma components and were strongly positive for WT‐1. The patient was advised to undergo chemotherapy and she was lost to follow‐up. Conclusion: A careful histological examination is necessary for an accurate diagnosis, which is based on morphology and extensive immunohistochemical studies. According to the literature, surgical excision alone seems reasonable as the prognosis of TWN is considered to be good. However, due to the spontaneous rupture of the ovarian cyst, chemotherapy of the patient after the first surgery was necessary in our case. Therefore, additional case studies are needed to clarify the standardized treatment of TWN. Abstract : Heterologous elements and typical histological pattern of the tumor from ovarian (A) hyaline cartilage tissue, (B) mature adipose tissue and cutaneous adnexal structures, (C) and (D) triphasic pattern of nephroblastoma with blastematous, epithelial and stromal components, (E) WT1 is strongly positive in epithelial and blastemal cells, (F) AE1/AE3 is strongly positive in epithelia component.